PENGARUH CITRA MEREK, WORD OF MOUTH DAN INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN NIVEA BODY LOTION DIKOTA BATAM - Angeli, Angeli; Saputra, Asron (LPPM Universitas Putera Batam, 2026)
This study aims to examine the influence of brand image, word of mouth, and product innovation on purchasing decisions of Nivea Body Lotion in Batam City. The research employs a quantitative approach using a survey method. Data were collected through the distribution of questionnaires to 196 respondents who are users of Nivea Body Lotion in Batam City. The data analysis method applied in this study is multiple linear regression using SPSS software. The results indicate that partially, brand image does not have a significant effect on purchasing decisions of Nivea Body Lotion in Batam City. In contrast, word of mouth and product innovation are proven to have a positive and significant influence on purchasing decisions. Simultaneously, brand image, word of mouth, and product innovation collectively have a significant effect on purchasing decisions of Nivea Body Lotion in Batam City. Keywords: Brand Image, Word of Mouth, Product Innovation and Purchasing Decisions.